Repetitive Maturation of Oocytes From Non-Stimulated Xenografted Ovarian Tissue From a Prepubertal Patient Indicating the Independence of Human Ovarian Tissue - Raffel, Nathalie; Lotz, Laura; Hoffmann, Inge; Liebenthron, Jana; Söder, Stephan; Beckmann, Matthias; Dittrich, Ralf (Geburtshilfe und Frauenheilkunde, 2017)
Introduction: Modern anti-cancer strategies have distinctly increased survival rates; nevertheless, often accompanied by sterility. Currently, the only option for preserving fertility in prepubertal females is to cryopreserve ovarian tissue and re-transplant frozen-thawed tissue to restore fertility after treatment. Our aim was to report the occurrence of repetitive antral follicle formation and oocyte maturation in a prepubescent ovarian tissue xenograft without exogenous hormone stimulation. Material and Methods: Frozen-thawed ovarian tissue from a 6-year-old patient suffering from nephroblastoma was xenotransplanted in oophorectomized severe combined immunodeficiency (SCID) mice to evaluate follicle development. Ergebnisse: Repetitive follicle development to the antral stage occurred in the same xenograft of prepubertal ovarian tissue without exogenous hormone administration; 37 days after retrieving a maturing oocyte (this first retrieval has been previously published), another, completely mature oocyte was harvested from the xenograft. Subsequent histological evaluation of the grafted tissue showed primordial follicles, nearly all stages of developing follicles, as well as large atretic ones. Many clusters with dormant primordial follicles were also present. Conclusion: Xenotransplanted prepubertal ovarian tissue has the potential for repetitive oocyte retrieval cycles without administering exogenous hormones. The results indicate that the human ovarian tissue might be able to synchronize the hypothalamus-hypophysis-axes of the mouse to the physiological human cycle; this should be investigated in future studies.
EVALuna2:34929